Conserved multisensory integration of social cues in the thalamus - Lukas Anneser; Johannes Maximilian Kappel (iScience)
Summary: The recognition of conspecifics, animals of the same species, and keeping track of changes in the social environment is essential to all animals. While molecules, circuits, and brain regions that control social behaviors across species are studied in-depth, the neural mechanisms that enable the recognition of social cues are largely obscure. Recent evidence suggests that social cues across sensory modalities converge in a thalamic area conserved across vertebrates. These thalamic neurons control social behavior both via direct synaptic projections to other brain areas relevant for social behavior and by exerting brain-wide neuropeptidergic modulatory influence. Conspecifics are recognized by auditory, visual, and somatosensory cues, as well as mechanosensory inputs. These inputs are mostly processed in the mammalian colliculi and homologous structures in other vertebrates and are subsequently integrated in the posterior thalamus. Increased neuronal activity in this area promotes pro-social behavior across vertebrates. We propose a framework for social cue recognition by conspecific frequency-tuning in the vertebrate thalamus, discuss the potential roles of these conserved social representations and point to open questions.